IgA-dominant Infection-related Glomerulonephritis in a 13-year-old Child: A Case Report and Brief Review of Literature: IgA-dominant Infection-related Glomerulonephritis - Magh , Ipshita; Priyadarshini, Lipsa; Pradhan, Subal Kumar (Journal of Pediatric Nephrology, 2024)
There has been a history of various bacterial infections and glomerular injuries, which are now pooled under the terminology of infection-related glomerulonephritis (IRGN). IRGN is an immune complex-mediated glomerulonephritis (GN) preceded by infection with subsequent recovery of renal function after the resolution of the infection. Pediatric IgAdominant infection associated with GN is rare and generally has a favorable prognosis compared to adults with severe comorbidities, like diabetic nephropathy. We reported a 13-year-old girl presented with acute kidney injury with nephritic features with no history of concurrent illness.